ANALYSIS OF FAMILY WELL-BEING IMPROVEMENT THROUGH THE JOINT ENTERPRISE GROUP PROGRAM (KUBE) IN HULOTHALANGI DISTRICT - Syamsul; Achmad Risa Mediansyah; Syaiful Pakaya (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2020)
The research objectives were to analyze the implementation of the joint enterprise group program (KUBE) in supporting family enterprise groups in Hulothalangi District, to analyze the benefits of the KUBE program in improving family well-being, and to analyze the obstacles faced by beneficiary families in developing their enterprise groups. The stages in the research method began with collecting data by using two approaches, namely, in-depth interview and focused group discussion. Administrators, members, government and stakeholders were conducted in In-depth interviews. Data analysis in this research used a descriptive-qualitative approach with Miles and Huberman's data analysis model consisting of data collection, data reduction, data display, and Conclution Drawing/Verification. The results showed that the thorough implementation of the KUBE program was not fully carried out seriously. The benefits of the KUBE program for groups have not yet been gained to increase family well-being. There are many obstacles that prevent the KUBE program from being implemented properly.